ANALISIS IMPLEMENTASI MEDIA PEMBELAJARAN MATEMATIKA BERBASIS GAME EDUKASI SCRATCH DALAM MENGINTEGRASIKAN AKTIVITAS DEEP LEARNING DI SEKOLAH DASAR - Michelle Miranda Elizabeth Matahelumual; Dian Anggraeni Maharbid (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the implementation of Scratch-based educational games in mathematics learning and how they integrate deep learning activities in elementary schools. Using a qualitative library research approach, this study reviews ten relevant national and international articles discussing Scratch media, mathematics learning, and deep learning frameworks. The findings show that Scratch effectively enhances students’ interest and engagement through interactive game-based learning. Scratch also strengthens conceptual understanding by providing visual and concrete representations that simplify abstract mathematical concepts. Furthermore, Scratch supports the development of higher-order thinking skills, including computational thinking, problem-solving, analysis, and metacognition. Collaborative learning is also encouraged as students interact, discuss, and work together in completing game challenges. Overall, the study concludes that Scratch is a highly potential digital learning medium that supports meaningful, reflective, and deep learning–oriented mathematics instruction in elementary schools.